UJI EFEK ANTELMINTIK EKSTRAK ETANOL BIJI PINANG (ARECA CATECHU) TERHADAP CACING ASCARIS LUMBRICOIDES DAN ASCARIDIA GALLI SECARA IN VITRO - Tiwow, Debra; Bodhi, Widdhi; Kojong, Novel (PHARMACON, 2013)
Betel nut (Areca catechu) known as folks medicine that possess anthelmintic activity.Anthelmintic were used to reduce or eliminate the worm in human or animal body. The aimsof this research were to find out anthelmintic activity of ethanol extract of betel nut againstAscaris lumbricoides and Ascaridia galli, and to determine efective concentration of ethanolextract of betel nut as an anthelmintic. This assay using ethanol extracts of betel nut withconcentration of 10%, 20%, and 30%. Mortality and paralysis percent of worms observedevery hour for 12 hours. Obtained data were analyzed by ANOVA. Regression analysis wasconducted to determine PC50 and LC50. The result show that ethanol extract of betel nutpossess an in vitro anthelmintic against Ascaris lumbricoides and Ascaridia galli. PC50 valuesobtained in Ascaris lumbricoides was 27.12%, and LC50 values obtained in Ascaridia galliwas 27.11% on worm for 12 hours.Keywords : Anthelmintic, ethanol extract of betel nut (Areca catechu), Ascaris lumbricoides,Ascaridia galli